Perspektif Budaya Bersalin di Boti Kabupaten Timor Tengah Selatan - Mareta Bakale Bakoil; Veki Edizon Tuhana (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Most deliveries in Timor Tengah Selatan Regency are still assisted by traditional birth attendants. The purpose of this study was to determine the perspective of maternity culture in Boti, Timor Tengah Selatan Regency. This type of research was phenomenology. Research informants were tribal chiefs, midwives and mothers who gave birth. Data were collected through in-depth interviews and then continued with thematic analysis. The results showed that when the mother was about to give birth, her family immediately called a traditional birth attendant because of the trust factor. Traditional birth attendants provide support and motivation to mothers during the delivery process. The position of the mother during childbirth is sitting on a stone that has been prepared by her husband, the umbilical cord is cut using bamboo, with a distance of three fingers. Furthermore, it was concluded that the Boti community had hereditary beliefs and cultures related to childbirth, namely giving birth at home, assisted by traditional birth attendants. Keywords: childbirth; culture; perspective ABSTRAK Sebagian besar persalinan di Kabupaten Timor Tengah Selatan masih ditolong oleh dukun bayi. Tujuan penelitian ini adalah mengetahui perspektif budaya bersalin di Boti Kabupaten Timor Tengah Selatan. Jenis penelitian ini adalah fenomenologi. Informan penelitian adalah kepala suku, bidan dan ibu bersalin. Data dikumpulkan melalui wawancara mendalam lalu dilanjutkan dengan analisis tematik. Hasil penelitian menunjukkan bahwa ketika ibu akan melahirkan, keluarganya segera memanggil dukun bayi karena faktor kepercayaan. Dukun bayi memberikan dukungan dan motivasi kepada ibu selama proses persalinan. Posisi ibu saat melahirkan yaitu duduk di atas batu yang telah disiapkan oleh suaminya, tali pusar dipotong menggunakan bambu, dengan jarak ruas tiga jari. Selanjutnya disimpulkan bahwa masyarakat Boti memiliki kepercayaan dan budaya turun-temurun yang berhubungan dengan persalinan yaitu melahirkan di rumah, ditolong dukun. Keywords: persalinan; budaya; perspektif